2004
DOI: 10.1007/s00426-004-0183-8
|View full text |Cite
|
Sign up to set email alerts
|

Distance cognition in virtual environmental space: Further investigations to clarify the route-angularity effect

Abstract: Two experiments with 72 participants in total investigated the route-angularity effect. This effect is shown when a greater number of turns along a route increase the estimated length of this route. In this study it was shown that the route-angularity effect is likely to be a memory-based effect depending on task difficulty. The important factor seems to be how heavily memory is loaded during learning. The route-angularity effect even appears in intentional learning, when memory is loaded heavily. Under this l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Though the authors have no reason to believe that these individuals would be more or less vulnerable to the number of turns when making estimates, continuing research should control or record participant location. Second, though this study's manipulation of number of turns did aff ord direct comparison to prior research (i.e., 2 vs 7 turns; Jansen- Osmann & Wiedenbauer, 2004a, 2004b, and extended this research by including 1, 3, and 5 turns, there may be benefi t to more fi nely incrementing the number of turns between 1 and 7. To the authors' knowledge, no research to date has precisely defi ned all number of turn increments within those limits.…”
Section: Resultsmentioning
confidence: 85%
“…Though the authors have no reason to believe that these individuals would be more or less vulnerable to the number of turns when making estimates, continuing research should control or record participant location. Second, though this study's manipulation of number of turns did aff ord direct comparison to prior research (i.e., 2 vs 7 turns; Jansen- Osmann & Wiedenbauer, 2004a, 2004b, and extended this research by including 1, 3, and 5 turns, there may be benefi t to more fi nely incrementing the number of turns between 1 and 7. To the authors' knowledge, no research to date has precisely defi ned all number of turn increments within those limits.…”
Section: Resultsmentioning
confidence: 85%
“…For example, Ruddle, Payne, and Jones (1997) could replicate the results of direction and distance knowledge obtained in real-world settings (Thorndyke & Hayes-Roth, 1982) in a virtual environment; May and Klatzky (2000) showed that the effect of irrelevant movements on path integration was similar in real and desktop virtual environments. Virtual environments allow participants to acquire distance knowledge (Jansen-Osmann & Berendt, 2002;Jansen-Osmann & Wiedenbauer, 2004a;Willemsen & Gooch, 2002), knowledge about directions (Albert, Rensink, & Beusmanns, 1999), and route and survey knowledge (Gillner & Mallot, 1998;Jansen-Osmann, 2002). However, there may also be drawbacks, especially when desktop virtual reality systems are used, and no proprioceptive sensory information is generated (Witmer, Bailey, Knerr, & Parsons, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Because metric representations are less durable, conditions that challenge memory systems are likely to result in relative reliance on non-metric memory codes. For example, Jansen-Osmann and Wiedenbauer (2006) observed an angularity effect when distance estimates were made after walking all paths (two turn, seven turn, reference), but no effect when estimates were made after each path. As participants walk and encode additional path lengths, the relative availability of fine-grained, metric spatial information decreases, and the influence of non-metric information (number of turns) emerges.…”
Section: Features Make Paths Seem Longermentioning
confidence: 99%
“…Sadalla and Staplin’s name frequency manipulation served to increase the relative availability of non-metric codes (how many names are associated with a given path), and thus increased the feature accumulation effect. Hutcheson and Wedell employed manipulations (concurrent tasks and filled delays) that served to decrease the relative availability of metric spatial codes, which also increased the feature accumulation effect (also see Jansen-Osmann & Wiedenbauer, 2006). Thus, the dual memory systems account suggests that the feature accumulation effect depends not only on the quantity of information associated with a route, but on the quality of that information as well.…”
Section: Features Make Paths Seem Longermentioning
confidence: 99%